Illicit financial flows and stolen asset recovery: The Global North must act - Abdul Muheet Chowdhary; Sebastien Babou Diasso (South Centre, 2022)
Domestic resource mobilization is essential for developing countries to achieve the Sustainable Development Goals by the deadline of 2030. Concomitantly, Illicit Financial Flows (IFFs), which also lead to asset theft, are major means through which these countries are losing resources. This research paper analyzes the World Bank's Stolen Asset Recovery (STAR) database and shows that countries from where assets have been stolen are mostly developing countries, and countries where the stolen assets have been hidden are developed countries. The paper also shows that regarding the pending or ongoing asset recovery cases, there is a clear pattern where the majority of countries waiting to have their assets returned are developing countries, and those who must return them are developed countries. There is an unexplained and unjustified delay by developed countries in the process of returning the frozen assets to developing countries which needs to be addressed as soon as possible. There is also an evaluation of international legal reforms which can be implemented to accelerate the asset recovery process. However, all these will need the full commitment of Global North countries where most of the stolen assets are hidden and which bear the brunt of responsibility for returning them to the developing countries.
Keywords: 300; Asset Recovery; Corporate Tax; Domestic Resource Mobilization; FACTI Panel; FACTI Recommendations; Global North; Global South; Global Tax; Global Taxation; High Level Panel on Illicit Financial Flows from Africa; HLP on International Financial Accountability Transparency and Integrity for Achieving 2030 Agenda (FACTI Panel); Illicit Financial Flows (IFFs); International Tax; International Tax Cooperation; International Tax Reform; International Taxation; Stolen Asset Recovery Initiative; Sustainable Development Goals (SDGs); Tax; Tax Cooperation; Tax Law; Tax Policy; Tax Reform; Taxation; UN Convention against Corruption